First rib removal and decompression of the thoracic outlet as an indication to facilitate hemodialysis - Seamus M. McHugh, MD; Mohamad A. Hussain, MD; Badr Aljabri, MD, FRCSC; Elisa Greco, MD, MEd, FRCSC; Mohammed Al-Omran, MD, MSc, FRCSC (Journal of Vascular Surgery Cases and Innovative Techniques, 2016)
We present two cases of thoracic outlet decompression performed to facilitate hemodialysis through upper limb arteriovenous fistulas. In patients undergoing arteriovenous fistula formation for dialysis access, venous hypertension is a well-known complication. We used a supraclavicular approach in our two reported cases to remove the first rib to facilitate hemodialysis. Dialysis patients presenting with central venous stenosis should be assessed for evidence of extrinsic compression by the first rib as management options differ from those with central venous stenosis due to an intravenous catheter.